Exploring the ER channel protein Sec61: recent advances in pathophysiological significance and novel pharmacological inhibitors - Xin, Jingxin; Yin, Keling; Li, Shimeng; Gu, Peiyuan; Shao, Shanshan (Frontiers in Pharmacology, 2025)
The Sec61 complex, which is located on the membrane of the mammalian endoplasmic reticulum (ER), serves as a pivotal component of protein transport channels. It plays a central role in the transport of nascent peptides and precursor peptides to the ER. This process includes the directed movement of precursor peptides to the ER membrane and the opening of the Sec61 transduction channel for translocation. The Sec61 channel not only plays a key role in transporting peptides into cells but also acts as a passive ER Ca2+ leak channel. In addition, the mutation, amplification and overexpression of Sec genes are closely related to the development of various genetic diseases and cancers. Over the past few decades, studies have elucidated the function of the Sec61 protein in the pathogenesis of diseases such as cancer, and Sec61 inhibitors have been developed for their treatment. This review describes the structure of Sec61 and its function in transporting ER transmembrane proteins and further summarizes the role of this gene in disease and recent advancements in Sec61 inhibitors. This study provides novel insights into the involvement of Sec61 in disease etiology and lays the groundwork for future treatment modalities targeting this pivotal protein complex.